Quality of Sulfadoxine-Pyrimethamine Given as Antimalarial Prophylaxis in Pregnant Women in Selected Health Facilities in Central Region of Ghana - Danny F. Yeboah; Richmond Afoakwah; Ekene K. Nwaefuna; Orish Verner; Johnson N. Boampong (Journal of Parasitology Research, 2016)
The use of sulfadoxine-pyrimethamine (SP) as an intermittent preventive treatment (IPT) against malaria during pregnancy has become a policy in most sub-Sahara African countries and crucially depends on the efficacy of SP. This study sets out to evaluate the effectiveness of the SP given to the pregnant women in some selected health facilities in the Central Region of Ghana to prevent maternal malaria in pregnant women. A total of 543 pregnant women recruited from 7 selected health centres in Central Region of Ghana participated in the study. Parasite density of Plasmodium falciparum was determined from peripheral blood of the pregnant women using microscopy. High performance liquid chromatography (HPLC) and dissolution tester were used to determine the quality of the SP. Malaria infection was recorded in 11.2% of pregnant women who had a history of SP consumption. SP failed the dissolution test. Pregnant women who did not receive IPT-SP were 44%. Low haemoglobin level was recorded in 73.5% of the pregnant women. The results indicated that SP was substandard. IPT-SP is ineffective in preventing malaria infection.